Dialog z tradycją w piosenkach zespołu Lao Che - Roszczynialska, Magdalena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2012)
The text explains how the Lao Che rock band tackles tradition in their so-called Polish Triptych. Analyzing the first album, the author shows how the band presents the Slavic tradition within the postcolonial framework. In the second one, she focuses on the depiction of the mythology of the Warsaw Uprising and the Polish historical policy based on it. The third album is dicussed in terms of failure of identity based on religious values, which refuses to acknolwedge the reality of cosumer society.